2020
DOI: 10.29141/2218-5003-2020-11-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of high-tech and medium-tech business models: Key indicators and value sustainability

Abstract: Due to the external environment being unpredictable and dynamic, the business model becomes obsolete in a short time and its logic loses effectiveness. This seriously threatens business continuity and affects income flows. The paper develops indicators for assessing the effectiveness of business models. Methodologically, the study rests on the stakeholder theory, valuebased management and technological growth theory. The work uses mathematical methods for calculating financial and economic indicators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In recent decades, the business sector is experiencing a revolution derived from technological and social trends towards digitization. This technological and digital transformation undergoes an intense readjustment in all functional areas, from production to finance and accounting [1,2]. Currently, the adoption of technologies by companies is related to a paradigm shift, where technology is perceived as a complex and interconnected environment at a global level [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the business sector is experiencing a revolution derived from technological and social trends towards digitization. This technological and digital transformation undergoes an intense readjustment in all functional areas, from production to finance and accounting [1,2]. Currently, the adoption of technologies by companies is related to a paradigm shift, where technology is perceived as a complex and interconnected environment at a global level [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In the review of the literature carried out, studies have been found that address this topic, so that the research questions on emerging technologies in corporate accounting refer to determining: (1) what is the knowledge structure of this topic; (2) which are the most productive journals, research institutions, and countries; and (3) which are the thematic axes that this research field develops and towards which are they evolving.…”
Section: Introductionmentioning
confidence: 99%